2023
DOI: 10.3390/ejihpe13090133
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Counseling among University Students Worldwide: A Systematic Review

Silvia Cerolini,
Andrea Zagaria,
Costanza Franchini
et al.

Abstract: University counseling services (UCSs) are actively involved in mental health assessment and in supplying interventions aimed at preventing, facing and possibly overcoming psychological problems. However, we do not have a global overview of psychological counseling among universities. This systematic review aims at reviewing the literature on university psychological counseling, including articles documenting: (1) mental health and attitudes regarding help-seeking behaviors and UCSs among university students or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 116 publications
0
1
0
Order By: Relevance
“…Psychological counseling centers at universities offer low-threshold help for students [ 68 ], and a recent systematic review confirmed the effectiveness of face-to-face and online counseling interventions in improving the mental health of university students [ 69 ]. A meta-analysis by Osborn and Saunders [ 70 ] showed that a good proportion of students use these services, but some barriers still exist, such as low help-seeking behavior and fear of stigmatization, low mental health literacy, or misconceptions about and lack of trust in counselors [ 69 ]. Because of the high prevalence of mental health disorders in students, there is an urgent need to expand these services.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…Psychological counseling centers at universities offer low-threshold help for students [ 68 ], and a recent systematic review confirmed the effectiveness of face-to-face and online counseling interventions in improving the mental health of university students [ 69 ]. A meta-analysis by Osborn and Saunders [ 70 ] showed that a good proportion of students use these services, but some barriers still exist, such as low help-seeking behavior and fear of stigmatization, low mental health literacy, or misconceptions about and lack of trust in counselors [ 69 ]. Because of the high prevalence of mental health disorders in students, there is an urgent need to expand these services.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%